Enhancing Teachers' Pedagogical Competence in Inclusive Education through Continuous Coaching - Khotimah, Khusnul; Purwanta, Edi (Papanda Publisher, 2025)
Despite widespread policy advocacy for inclusive education, significant challenges persist in implementation, particularly regarding teachers' pedagogical competencies to effectively serve students with diverse learning needs. This study addresses the critical gap in continuous coaching programs specifically designed for inclusive education contexts in early childhood settings. This research investigates the effectiveness of continuous coaching in enhancing teachers' pedagogical competencies for inclusive education implementation at Daarussalaam Islamic Integrated Kindergarten. The study employed School Action Research methodology using the Kemmis and McTaggart model, conducting three cycles of planning, action, observation, and reflection over three months. Five kindergarten teachers participated in the intervention, with data collected through observation sheets, semi-structured interviews, competency evaluation instruments, and teacher reflection journals. Each cycle incorporated training sessions, supervision, mentoring, and group discussions, with teachers applying learned strategies in inclusive classrooms. The intervention achieved remarkable success, with all teachers advancing from